2013
DOI: 10.1002/berj.3031
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal association of childhood school engagement with adult educational and occupational achievement: findings from an Australian national study

Abstract: The research investigated the association between school engagement and adult education and occupation outcomes, within the context of a 1985 Australian longitudinal national cohort study of the factors affecting children's long‐term health and well‐being. School engagement may be more modifiable than other factors related to academic success, such as academic attainment, which is influenced by family background. A School Engagement Index was constructed using questionnaire items on school enjoyment and boredo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 54 publications
0
64
0
3
Order By: Relevance
“…Teachers were also noted as being engaging when they were fun, had a sense of humour, and related in ways that were not 'boring', such as having excitement in their voices. On the surface, the findings in this theme could appear to trivialize learning and teachers, yet research confirms the improvement in outcomes when students are engaged in learning that is enjoyable, interesting, and challenging, with teachers they can relate to (Abbott-Chapman et al, 2014). Particularly pertinent to this theme is a contention by Abbott-Chapman et al (2014: 116) that enjoyment, as an expression of engagement, 'appears to further influence subsequent education and career choices well into adulthood'.…”
Section: Interesting and Funmentioning
confidence: 95%
See 2 more Smart Citations
“…Teachers were also noted as being engaging when they were fun, had a sense of humour, and related in ways that were not 'boring', such as having excitement in their voices. On the surface, the findings in this theme could appear to trivialize learning and teachers, yet research confirms the improvement in outcomes when students are engaged in learning that is enjoyable, interesting, and challenging, with teachers they can relate to (Abbott-Chapman et al, 2014). Particularly pertinent to this theme is a contention by Abbott-Chapman et al (2014: 116) that enjoyment, as an expression of engagement, 'appears to further influence subsequent education and career choices well into adulthood'.…”
Section: Interesting and Funmentioning
confidence: 95%
“…The provision of diverse applied learning opportunities is considered a modifiable aspect of schools' learning environments that promotes students' active participation (Abbott-Chapman et al, 2014). As one student explained: 'I like being active instead of angry teachers telling you this boring stuff you don't like' (9 I 3).…”
Section: Practical and Hands-on Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre los recursos positivos o fortalezas del alumnado que permiten adquirir un funcionamiento óptimo en el entorno educativo destaca la implicación escolar (school engagement), que ha sido identificada como un elemento clave para la adaptación y el éxito académico (Motti-Stefadini y Masten, 2013; Ros, Goikoetxea, Gairín y Lekue, 2012), así como para el éxito en los resultados alcanzados posteriormente en la edad adulta, tales como estudios superiores, mejores posibilidades de empleo, autopercepciones positivas y bienestar (Abbott-Chapman et al, 2014;SalmelaAro y Upadyaya, 2012;Wang y Peck, 2013). El consenso mayoritario en la comunidad científica reconoce la naturaleza multifacética del concepto (Lewis, Huebner, Malone y Valois, 2011;Wang, Willet y Eccles 2011), proponiéndose tres dimensiones: cognitiva, emocional y conductual (Appleton, 2012;Fredricks, Blumenfeld y Paris, 2004;González y Verónica-Paoloni, 2015).…”
Section: Introductionunclassified
“…Elovainio et al reported that negative aspects of school such as a lower academic score, repeating a class and absences were associated with lower job control, higher job demand or greater job strain in early midlife 6. We have previously shown that some positive school experiences, namely, higher childhood school engagement, predicted higher adult education and occupation status,8 so they may also be important for job stress, but this has not been examined.…”
mentioning
confidence: 95%